2023
DOI: 10.3390/jcm12030965
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and White Blood Cell Count in Cardiogenic Shock

Abstract: This study examines the prognostic impact of C-reactive protein (CRP) and white blood cell (WBC) counts in patients with cardiogenic shock (CS). Data regarding the prognostic impact of inflammatory biomarkers in CS are scarce. All consecutive patients with CS from 2019 to 2021 admitted to a cardiac intensive care unit (ICU) were included at one institution. Laboratory measurements were retrieved from the day of admission (i.e., day 1), as well as days 2, 3, 4, and 8. The primary endpoint was 30-day all-cause m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In clinic routine, CRP is frequently measured as a diagnostic tool for infection, as a marker for disease severity, as well as for the assessment of the therapeutic response (i.e., following antibiotic therapy) [ 9 ]. Even in patients with cardiogenic shock, increasing CRP was recently shown to indicate increased short-term mortality [ 10 ]. Within a meta-analysis including 9 studies and 1,368 patients, CRP was shown to have a moderate accuracy for the diagnosis of sepsis (area under the curve (AUC) = 0.73), while the diagnostic accuracy of procalcitonin (PCT) was higher (AUC = 0.85) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinic routine, CRP is frequently measured as a diagnostic tool for infection, as a marker for disease severity, as well as for the assessment of the therapeutic response (i.e., following antibiotic therapy) [ 9 ]. Even in patients with cardiogenic shock, increasing CRP was recently shown to indicate increased short-term mortality [ 10 ]. Within a meta-analysis including 9 studies and 1,368 patients, CRP was shown to have a moderate accuracy for the diagnosis of sepsis (area under the curve (AUC) = 0.73), while the diagnostic accuracy of procalcitonin (PCT) was higher (AUC = 0.85) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have employed different approaches to dividing the population when establishing the cut-off values for WBC counts. Whereas some studies used a range of normal WBC values (4.0-10.0 × 10^9/L) [27], others separated the population into quartiles [33]. The different grouping criteria used in these studies may have resulted in biased data and confounding variables between the groups, leading to variations in observations.…”
Section: Discussionmentioning
confidence: 99%
“…The present study prospectively included all consecutive patients presenting with CS on admission to the cardiac ICU at the University Medical Center Mannheim, Germany, from June 2019 to May 2021 [23,24]. All relevant clinical data related to the index event were documented using the electronic hospital information system as well as the IntelliSpace Critical Care and anesthesia information system (ICCA, Philips, Philips GmbH Market DACH, Hamburg, Germany) implemented at the ICU, organizing patient data such as admission documents, vital signs, laboratory values, treatment data, and consult notes.…”
Section: Study Patients Design and Data Collectionmentioning
confidence: 99%